Type designations and taxonomic remarks for Nearctic sap beetles in the subfamily Carpophilinae Erichson (Coleoptera: Nitidulidae) - Powell, Gareth S.; Cline, Andrew R. (Zootaxa, 2017)
The subfamily Carpophilinae, in particular the genus Carpophilus Stephens, represents one of the most speciose lineages within Nitidulidae. The subfamily is comprised of more than 250 described species that are found worldwide in every habitable region, and have been transported by man in stored products to remote islands and archipelagos (Ewing & Cline 2005; Parsons 1943). The ubiquitous Carpophilus dimidiatus (L.) is an example of a cosmopolitan species that has been reported from every continent except Antarctica, but likely has been transported there as well. Members of Carpophilinae are well recognized by their abbreviated elytra, compact bodies, and distinct three-segmented antennal club. Many taxa are present in fermenting food products and dried goods. Some members are also commonly found in flowering plants such as cacti, cycads, and agricultural plants such as atemoya (a hybrid of sugar-apple and cherimoya) (Nagel et al. 1989).